A Rare Case of Primary Mantle Cell Lymphoma of the Prostate: Clinical Aspects and Open Problems. Issue 3 (July 2013) - Gurioli, Alberto; Marson, Francesco; Pisano, Francesca; Soria, Francesco; Lorenzo, Daniele; Pacchioni, Donatella; Frea, Bruno; Gontero, Paolo
A case of primary prostate involvement by mantle-cell lymphoma diagnosed at the time of transvesical adenomectomy is reported. Diagnostic difficulties and clinical outcome are also presented. The possibility of prostate involvement by malignant lymphomas, albeit rare, should be considered in any case of histological evidence of dense prostate lymphoid infiltrate in patients with lower urinary tract obstruction, and should be highly suspected in patients with prior history of systemic lymphoma. Immunohistochemical analysis is essential for a correct diagnosis. Both urologists and pathologists should be aware of the existence of such a rare clinical condition.